Sistem Pendukung Keputusan Penerima Beasiswa BAZNAS Menggunakan Metode Technique For Others Reference By Similarity To Ideal Solution (Topsis) di SMKN 1 Batusangkar - Putri, Weskia Sefiola; Mery, Thomson; Samudra, Ami Anggraini (Universitas Labuhanbatu, 2024)
The problems at SMKN 1 Batusangkar in selecting students who are entitled to receive scholarships require a very long time and are inefficient, namely the committee will examine the document files submitted by students so that this makes it difficult for school administration staff to determine which students are entitled to receive assistance. and takes a long time in the selection process. A decision support system is an interactive system capable of making decisions through the use of data and decision models to solve semi-structured or unstructured problems. The method used in this design is a Decision Support System (SPK), namely the Software Development Life Cycle (SDLC). System design is made with a modeling language using the Unified Modeling Language (UML). The Technique For Others References By Similarity To Ideal Solution (TOPSIS) method was chosen which considered the positive and negative ideal solutions. In testing the system in this study using black box testing, white box testing and beta testing.